Comparison of microstructure and oxidation behavior between Pt-free and Pt-modified δ-Ni2Si coatings on Ni-based superalloys. (September 2015) - Fu, C.; Wang, C.H.; Ren, Z.M.; Cao, G.H.
Highlights: Pt decreases the chemical activity of Al to promote Al uphill diffusion. Pt improves the oxidation resistance of the Pt-modified δ-Ni2 Si coatings. Al-rich layer is formed in the Pt-modified δ-Ni2 Si coatings. Al-depleted and Cr-rich layers are formed in the Pt-free δ-Ni2 Si coatings. Abstract: This study investigated the microstructure and oxidation behavior of Pt-free and Pt-modified δ-Ni2 Si coatings prepared by codeposition of Al and Si. The composition (in wt.%) of packs was 1Al–4NH4 Cl– x Si-(95 −  x )Al2 O3 with different Si levels ( x  = 4, 6, 8, 10). Pt promotes uphill diffusion of Al in Pt-modified coatings while Cr tends to outward diffuse into Pt-free coatings. The isothermal oxidation tests indicated the coating with 10 wt.% Si had good oxidation performance. After oxidation, the microstructure of Pt-modified coatings was Cr2 NiO4  + NiO or Cr2 NiO4  + NiO + Al2 O3 while that of Pt-free coatings was Cr2 O3  + Ni31 Si12  + Al2 O3 .